Feasibility of a computer-assisted alcohol screening, brief intervention and referral to treatment program for DWI offenders. Issue 1 (December 2015) - Mullen, Jillian; Ryan, Stacy; Mathias, Charles; Dougherty, Donald
Abstract Background Alcohol use patterns that are hazardous for one's health is prevalent among DWI (driving while intoxicated) offenders and is a key predictor of recidivism. The aim of this program evaluation was to determine the feasibility and usability of implementing a computer-assisted screening, brief intervention and referral to treatment (SBIRT) program for DWI offenders to enable the identification of those in need of treatment services soon after arrest. Our treatment program consisted of a web-based, self-guided screening tool for assessing alcohol use patterns and generating a personalized feedback report that is then used to deliver a brief motivational intervention and if needed, a referral to treatment. Methods Between August and November 2014, all DWI offenders attending orientation for pre-trial supervision were assessed for eligibility. Of the 129 eligible offenders, 53.5 percent enrolled and the first 50 were asked to complete a usability and satisfaction questionnaire. Results The results demonstrated that the majority of those screened reported at-risk alcohol use patterns requiring referral to treatment. Clients reported high ratings of usability and satisfaction with the screening tool and personalized feedback report, which did not significantly differ depending on alcohol use patterns. There were relatively few technical difficulties, and the majority of clients reported high levels of satisfaction with the overall SBIRT program. Conclusion Results of this program evaluation suggest that computer-assisted SBIRT may be successfully implemented within the criminal justice system to DWI offenders soon after arrest; however, further research is required to examine its effects on treatment utilization and recidivism.